Indonesian Agricultural Industry Innovation to Create World Food Storage in 2045 - Dandi, Muh Zulhamdi Suhafid; Musabbihah, Mulkis (International Journal of Applied and Scientific Research, 2024)
The issue of food safety and food security has become an international concern, given the increasing global food demand due to the food crisis caused by the Covid 19 pandemic. Indonesia is trying to become a global food supplier through the Indonesian government's vision of "World Food Barn 2045". This article uses the approach of the theoretical debate between Ester Boserup, Mark Nathan Cohen, Michael Lipton, Parker G. Marden, and Warren C. Robinson which states that there is a relationship between variables of food availability, changes in agricultural technology, and population growth in the world. The results of the author's research in this article assume that in handling the issue of the global food crisis it is necessary for each country to sustain the event, Indonesia seeks to sustain the global food crisis through the implementation of an "Integrated Agriculture System" that integrates the agricultural sector and the livestock sector.